MAHASISWA JPOK FKIP UNS SEMESTER VI BELUM SLAP MENGAJAR - Mukholid, Agus (Jurnal Phederal Penjas, 2008)
This research purposes to find the answer of (1) how is the students' perception of major POK FKIP UNS about the implementation micro teaching?; and (2) how is students' interest of major POK FKIP UNS to become a teacher? This research is conducted in college of major POK FKIP UNS in 2006. The approach used is by using descriptive method and technique in collecting the data by using questionnaire and interview. This research variable is the students' interest about teacher profession. The analysis of research result is using the analysis technique of descriptive qualitative. The research results show that: (1) theoretically, the micro teaching has been understood by the student